Direct selection of Clostridium acetobutylicum fermentation mutants by a proton suicide method - Cueto, P.H. (1990)
Clostridium acetobutylicum ATCC 10132 mutants altered in acetic acid synthesis or in the shift to solventogenesis were directly selected by a proton suicide method after mutagenic treatment, by using bromide and bromate as selective agents. The mutants were characterized according to their solvent and acid production. On the selection plates they differed in colony phenotype from the parent strain.